Pengaruh Pengembangan Karir dan Tingkat Pendidikan Terhadap Kinerja Pegawai: (Studi Kasus pada RSUD Bandar Negara Husada Provinsi Lampung) - Dea Try Sela; M Yusuf Barusman (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study is based on the importance of human resource quality in supporting optimal health services, where variations in educational level and unequal career development are presumed to affect employee performance. The study employed a quantitative approach using an associative research method. The research population consisted of all employees of RSUD Bandar Negara Husada Province of Lampung totaling 216 employees, with a sample of 68 respondents determined using the Slovin formula and simple random sampling technique. The results indicate that career development has a positive and significant effect on employee performance. Educational level also has a positive and significant effect on employee performance. Simultaneously, career development and educational level have a positive and significant effect on the performance of employees at RSUD Bandar Negara Husada Province of Lampung. These findings indicate that improving employee performance can be achieved through structured career development management as well as enhancing the quality of education and employee competencies. Therefore, hospitals are advised to strengthen sustainable human resource development policies to improve employee performance and the quality of health services.